Systematic Review of Varied Exercise Programs on Body Composition and Physical Fitness for Firefighters - Seung-Hee Baek; Jung-Jun Park; Deong-Il Seo; Wook Song; Chung Gun Lee; Han-Joon Lee; Yeon Soon Ahn; Hyun-Joo Kang (Asian Society of Kinesiology, 2018)
OBJECTIVES Firefighting is one of the most hazardous, physically demanding professions that must possess relatively high levels of physical fitness to perform in a safe and efficient manner. Considering the intense nature of their work, firefighters requires regular exercise training to ensure optimal levels of occupational performance. This study suggests effective guidelines in different exercise programs for preventing injury and improving physical fitness through a systematic review of precedent literature about firefighters. METHODS In this systematic review, the Cochran's PICOTS-SD method (2009), which is based on precedent literature published by many researches was selected. We revised using appropriate key words from precedent literature for our present study. Finally, seven studies were selected from articles based on the time period from 2001 to 2018.2, Institutional Review Board (IRB) approval or randomly assigned. RESULTS Results showed useful information in the exercise field through analyzing exercise programs. Health-related physical fitness in firefighters showed significant differences before and after exercise participation, such as muscular fitness, cardiorespiratory fitness, and body composition. CONCLUSIONS The research suggest that an exercise program for firefighters could ensure optimal levels of occupational performance and endurance. It is hoped that the results of these studies will encourage those firefighters who are responsible for the public's safety to participate in required exercise programs.